Constructing Masculinity: A Barthesian Semiotic Analysis of Dior Sauvage Advertisement - Anne Pratiwi; Ulil Amri; Andina Meutia Hawa; Dyani Prades Pratiwi; Fakhria Nessa (Universitas Islam Sumatera Utara, 2026)
This study explores the construction of meaning through verbal and non-verbal signs in the Dior Sauvage advertisement featuring Johnny Depp. The research is grounded in Roland Barthes’ semiotic framework, which examines meaning at the levels of denotation, connotation, and myth. The study addresses how linguistic and visual elements within the advertisement construct and reinforce representations of masculinity. Employing a qualitative descriptive method, the data were collected from selected scenes focusing on verbal signs, such as brand naming and lexical choices, as well as non-verbal signs, including color, setting, costume, and body language. The findings reveal that the advertisement constructs masculinity through signs associated with strength, mystery, freedom, and independence. At the mythological level, the advertisement reinforces an ideological representation of ideal masculinity as dominant, emotionally restrained, and deeply connected to nature. The study concludes that meaning in advertising is not naturally inherent but socially and culturally produced through interconnected systems of signs that shape audience perceptions and ideological understanding.